E-Learning Dalam Persepsi Mahasiswa Pendidikan Jasmani - Cendra, Romi; Gazali, Novri; Solihin (UIR Press, 2020)
This study aims to look at the perception of Physical Education students using e-learning in the learning process. Type of quantitative descriptive research. The research location was carried out in the Physical Education Study Program FKIP Universitas Islam Riau. While the sample in this study was a class of 2017/2018 students totaling 155 people, with a total sampling technique. The stages of the research were carried out in three stages, namely: (1) pre-field; (2) field work; and (3) data analysis. Data collection techniques using attitude scale questionnaire. The data analysis method used is descriptive statistics, these statistics are intended to collect data, present data and determine value. The results of the study are outlined in 4 categories: strongly agree, agree, disagree, and strongly disagree. Based on the data analysis that has been done 98% of students agree to use e-learning in learning, it can be concluded that students' perceptions about the use of e-learning as a technology-based learning media really provide convenience to improve the quality of their learning, because e-learning is easily accessed anytime without being limited space and time. In terms of the content available on e-learning as well as the usefulness of e-learning in the learning process, it is very easy for students to find information, discuss online, and upload assignments and can save student costs in printing the paper assignments given by their lecturers.